Effect of Risk Preference, Professional Domination, Information, and Professional Relationship on Ethical Decision Making of Tax Consultants - Aksiana, Ida Bagus Widhi; Sujana, I Ketut (International research journal of management, IT and social sciences, 2019)
The purpose of this study was to determine the effect of risk preferences, professional dominance, current information, and professional relationships on tax consultant ethical decision making. This study uses a saturated sampling method with respondents being Tax Consultants Registered at the Indonesian Tax Consultant Association in the Bali Nusa Tenggara Region. Data collection methods used are questionnaires and data analysis using multiple linear regression. The results showed that risk preferences negatively affected the tax consultant's ethical decision making. Professional domination has a negative effect on tax consultant ethical decision making. Present information has a positive effect on tax consultant ethical decision making. Professional relations have a negative effect on tax consultant ethical decision making.